Review of the Implementation of Electronic Medical Records at RSU Banyumanik 2 Semarang in 2024 - Nuraeni, Puspa Ayu; Fani, Tiara (Universitas Muhammadiyah Sidoarjo, 2024)
PMK No. 24 of 2022 requires all health services to implement electronic medical records no later than the end of 2023. RSU Banyumanik 2 Semarang has been using an electronic medical record system since 2022 with SIMRS called SIM KHANZA. The aim of this research is to describe the implementation of electronic medical records at RSU Banyumanik 2 Semarang in 2024. This research is qualitative research with a case study approach. Data were collected by interviewing the head of the medical records installation, and a questionnaire to measure knowledge of 7 medical records officers and 41 nurses. Interview data analysis was carried out using the content analysis method. Characteristic data analysis is presented in the frequency distribution table. The results show that the majority or 87.5% of respondents have good knowledge about the implementation of Electronic Medical Records. The Hospital has provided an operational budget for Electronic Medical Records. SIMRS RSU Banyumanik 2 Semarang is called SIM KHANZA where all medical record sheets are generally integrated, except for Informed Consent because it relates to clarity of authentication for both doctor and patient. Infrastructure is available in all service units that use Electronic Medical Records. Suggestions, hospitals should regularly monitor facilities and infrastructure every week, upgrade computer specifications with larger data storage capacity so that service is fast and uninterrupted.